Realization of SVM Algorithm for Indirect Matrix Converter and Its Application in Power Factor Control. (9th September 2015) - Li, Gang
Abstract : Compared with AC-DC-AC converter, matrix converter (MC) has several advantages for its bidirectional power flow, controllable power factor, and the absence of large energy storage in dc-link. The topology of MC includes direct matrix converter (DMC) and indirect matrix converter (IMC). IMC has received great attention worldwide because of its easy implementation and safe commutation. Space vector PWM (SVM) algorithm for indirect matrix converter is realized on DSP and CPLD platform in this paper. The control of the rectifier and inverter in IMC can be decoupled because of the intermediate dc-link. The space vector modulation scheme for IMC is discussed and the PWM sequences for the rectifier and inverter are generated. And a two-step commutation of zero current switching (ZCS) in the rectifier is achieved. Input power factor of IMC can be changed by adjusting the angle of the reference current vector. Experimental tests have been conducted on a RB-IGBT based indirect matrix converter prototype. The results verify the performance of the SVM algorithm and the ability of power factor correction.